A Rare and Challenging Ectopic Variceal Hemorrhage: A Case Report - Christopher Pavel; Oana Mihaela Plotogea; Ecaterina Mihaela Rinja; Cosmin-Viorel Bogu; Andrei Turcescu (Reports)
Background and Clinical Significance: Ectopic variceal bleeding is a rare, but regrettably life-threatening, complication of hepatic cirrhosis. There is no standardized approach to this life-threatening event due to the absence of randomized controlled trials. Prompt identification of the bleeding site is crucial for timely hemostasis using endoscopic, radiologic or surgical methods. Case presentation: Throughout this paper, we present the case of a 52-year-old patient with decompensated alcoholic cirrhosis, who was admitted for melena. Upper and lower endoscopy failed to identify the source of bleeding. Ultimately, an evaluation with endoscopic capsule identified ileal varices. The patient was referred to surgery and the outcome was successful. We approached the diagnostic and therapeutic arsenals in managing ectopic varices. Conclusions: Although ectopic variceal bleeding has a substantial potential for fatal outcomes, prompt intervention in a multidisciplinary team could be the key for patient salvation.